Razvojni potenciali slovenskega podjetništva: Slovenski podjetniški observatorij 2011/12 - Tominc, Polona; Močnik, Dijana; Bradač Hojnik, Barbara; Korez-Vide, Romana; Štrulelj, Tjaša; Hauptman, Lidija (University of Maribor Press, 2012)
Developmental Potential of Slovenian Entrepreneurship : Slovenian Entrepreneurship Observatory 2011/12. In this monograph, we first analysed all the companies and entrepreneurs in Slovenia in 2010. Afterwards, for 2008, we compared the data for companies from Slovenia and the EU-27 in the activities of industry, trade, and services. Additionally, the insight into particular industries was done with the analysis of cultural and creative industries in Slovenia and compared to other European countries. We established that they are in Slovenia still in developmental phase. In the third chapter, analysed are that innovations, their importance for improving the competitive position of Slovenian enterprises and needs for their promotion with the appropriate education and economic policy measures. In the last chapter provided is the analysis of efficiency and performance of the Single Market of the European Union, which is of key importance for economic growth and companies’ development. The indicators of the Single Market from the European Commission’s database SBA Fact Sheet 2010/11 show that Slovenia achieves better results compared to the EU-27’s average in the Single Market field.